Motivations, understandings, and experiences of open‐access mega‐journal authors: Results of a large‐scale survey. (22nd January 2019) - Wakeling, Simon; Creaser, Claire; Pinfield, Stephen; Fry, Jenny; Spezi, Valérie; Willett, Peter; Paramita, Monica
Abstract : Open‐access mega‐journals (OAMJs) are characterized by their large scale, wide scope, open‐access (OA) business model, and "soundness‐only" peer review. The last of these controversially discounts the novelty, significance, and relevance of submitted articles and assesses only their "soundness." This article reports the results of an international survey of authors ( n = 11, 883), comparing the responses of OAMJ authors with those of other OA and subscription journals, and drawing comparisons between different OAMJs. Strikingly, OAMJ authors showed a low understanding of soundness‐only peer review: two‐thirds believed OAMJs took into account novelty, significance, and relevance, although there were marked geographical variations. Author satisfaction with OAMJs, however, was high, with more than 80% of OAMJ authors saying they would publish again in the same journal, although there were variations by title, and levels were slightly lower than subscription journals (over 90%). Their reasons for choosing to publish in OAMJs included a wide variety of factors, not significantly different from reasons given by authors of other journals, with the most important including the quality of the journal and quality of peer review. About half of OAMJ articles had been submitted elsewhere before submission to the OAMJ with some evidence of a "cascade" of articles between journals from the same publisher.